Surface-termination-dependent stability and band alignment in CsPbX3 (X = I, Br, Cl) perovskites: A first-principle study. (September 2020) - Nazari, Safieh; Azar, Yavar T.; Doroudi, Alireza
Abstract : Graphical abstract: Abstract: Recently, cesium metal halides have shown the potential application in photovoltaic and optoelectronic devices. The low stability of these all-inorganic materials in the ambient condition is the main barrier that can be overcome by dimension reduction. Herein, employing density functional theory the stability and electronic structure of α -CsPbX 3 (X = Cl, Br, and I) 2D slabs are investigated systematically as a function of halogen-type and surface termination. The surface energies and charge distributions over the atomic layers are calculated for all slab models and based on the partial charge assigned to each atomic layer, two different polarization patterns were established for CsX- and PbX 2 -terminated surfaces. The results reveal that CsX-terminated surfaces are more stable and show better band alignment for photovoltaic applications. Also, compositional bandgap modification is demonstrated for this category of 2D perovskites. The outcome is beneficial for structural engineering, bandgap modulation, and understanding of the underlying mechanism of the interfacial charge transfer in CsPbX 3 -based devices.